The Effect of Religiosity, Halal Certificate, Halal Awareness, on Purchasing Intention with Mediated Attitude Variables (Study on Holland Bakery) - Widad, Sarah; Asih, Daru (Dinasti Publisher, 2023)
Food is a source of energy needed for the human body and is one of the basic needs of life. For muslims, it is highly recommended to consume halal food. Halal food seems to be the most important sector of the food industry. To find out whether food is halal or haram, information is needed that can show that the food is halal for consumption by muslims. Halal certification is important for muslim consumers in determining the choice of food packaging products. After reviewing previous research, the research objective was determined, namely to analyze the influence of religiosity, halal certificate, halal awareness, through attitudes as an intervening factor in purchasing intentions. The population is Holland Bakery consumers. The sample unit taken was 130 respondents. Data analysis using SEM with the PLS program. The results obtained reflect the factors of religiosity, halal certificate, halal awareness, through attitudes as an intervening factor in purchasing intentions.